2002
DOI: 10.1074/jbc.m200128200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Overlap between Retinitis Pigmentosa 2 Protein and the Tubulin-specific Chaperone Cofactor C

Abstract: Mutations in the X-linked retinitis pigmentosa 2 gene cause progressive degeneration of photoreceptor cells. The retinitis pigmentosa 2 protein (RP2) is similar in sequence to the tubulin-specific chaperone cofactor C. Together with cofactors D and E, cofactor C stimulates the GTPase activity of native tubulin, a reaction regulated by ADP-ribosylation factor-like 2 protein. Here we show that in the presence of cofactor D, RP2 protein also stimulates the GTPase activity of tubulin. We find that this function is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 45 publications
3
102
0
Order By: Relevance
“…47 These and other data from experiments with Saccharomyces cerevisiae indicated that RP2 and cofactor C have overlapping functions, in addition to other functions that are specific to each molecule. It was also shown that RP2 reacts with ADPribosylation factor-like 3-protein, when the latter protein is bound to GTP.…”
Section: X-linked Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…47 These and other data from experiments with Saccharomyces cerevisiae indicated that RP2 and cofactor C have overlapping functions, in addition to other functions that are specific to each molecule. It was also shown that RP2 reacts with ADPribosylation factor-like 3-protein, when the latter protein is bound to GTP.…”
Section: X-linked Retinitis Pigmentosamentioning
confidence: 99%
“…46 The N-terminal segment of RP2 has similarity with cofactor C, which in humans is one of a set of at least five chaperones (A through E) involved in tubulin folding. 46,47 Cofactors C and D activate tubulin GTPase (hence they are called GTPase activator proteins, or GAP). RP2, together with cofactor D, serves as the GAP for tubulin, meaning that RP2 can replace cofactor C. Although RP2 replaced cofactor C to act as GAP in conjunction with cofactor D, RP2 did not catalyze tubulin heterodimerization as cofactor C did.…”
Section: X-linked Retinitis Pigmentosamentioning
confidence: 99%
“…In a yeast complementation assay, RP2 was shown to partially complement the CIN2 (tbcc homolog) deletion. However, unlike TBCC, RP2 does not promote tubulin heterodimerization in vitro (111). The GAP activity of RP2 and TBCC relies on the TBCC domain and many of the RP2 mutations involved in the retinitis pigmentosa pathology occur in this domain (109).…”
Section: The Ciliary Roles Of Tubulin Folding Pathway Members and Relmentioning
confidence: 99%
“…The structure of RP2 reveals two major domains: an amino-terminal domain homologous to tubulin binding cofactor C (TBCC) homology domain and a carboxyl-terminal nucleoside diphosphate kinase domain [77][78][79] (Figure 3). The purified RP2 protein possesses GTPase activating protein (GAP) activity towards the small GTPase ARL3 (ADP Ribosylation FactorLike protein 3).…”
Section: Rp2mentioning
confidence: 99%